2008
DOI: 10.1016/j.drugalcdep.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of two universal randomized first- and second-grade classroom interventions on young adult suicide ideation and attempts

Abstract: Objective-This paper reports the impact of two first-and second-grade classroom based universal preventive interventions on the risk of Suicide Ideation (SI) and Suicide Attempts (SA) by young adulthood. The Good Behavior Game (GBG) was directed at socializing children for the student role and reducing aggressive, disruptive behavior. Mastery Learning (ML) was aimed at improving academic achievement. Both were implemented by the teacher.⋆ Supplementary data on the second cohort can be accessed with the online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(153 citation statements)
references
References 76 publications
8
135
0
3
Order By: Relevance
“…Even if no interactive impact with baseline individual level risk is found, individual level risk may affect outcomes as a main effect. Even when the outcome is far removed in time from the intervention period, there can be dramatic continuities of these antecedent risks over time, as we have found in our analyses of the role of aggressive, disruptive behavior in the long-term effects of the GBG Petras et al, 2008;Poduska et al, 2008;Wilcox et al, 2008).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Even if no interactive impact with baseline individual level risk is found, individual level risk may affect outcomes as a main effect. Even when the outcome is far removed in time from the intervention period, there can be dramatic continuities of these antecedent risks over time, as we have found in our analyses of the role of aggressive, disruptive behavior in the long-term effects of the GBG Petras et al, 2008;Poduska et al, 2008;Wilcox et al, 2008).…”
Section: Discussionmentioning
confidence: 59%
“…Only the ML classrooms were excluded because they provided no information about the GBG impact nor could they be used as controls because of ML's own potential impact. In Wilcox et al (2008), ML classes were included since hypotheses about this intervention were also tested. In Petras et al (2008) the GBG analyses were based on comparisons between the GBG classrooms and the internal GBG controls.…”
Section: Denominator At the Level Of Randomization For Itt Analysesmentioning
confidence: 99%
“…Kellam and colleagues found that the GBG was associated with greater likelihood of a range of positive outcomes, including lower alcohol and substance use or dependence, reduced smoking, lowered incidence of Antisocial Personality Disorder (ASPD) and improved graduation rate , as well as reduced engagement in high-risk sexual behaviors and lowered incidence of drug dependence disorders (Kellam et al, 2014) and reduced suicide ideation and attempt by age 19-21 (Wilcox et al, 2008). Another trial found that when compared to a family-school partnership or control group, students who received the GBG throughout grade 1 had significantly higher college attendance rates and reduced likelihood of special education placement than both groups (Bradshaw, Zmuda, Kellam & Ialongo, 2009).…”
Section: Long Term Outcomesmentioning
confidence: 99%
“…School-based interventions involving social skills training to change behavior, such as the Good Behavior Game [37], have shown long-term effects on externalizing behavior. Furthermore, mental health services provided by school-based health centers have been shown to improve academic outcomes [38].…”
Section: Policy Implicationsmentioning
confidence: 99%